Study of acylhydrazone derivatives with deoxygenated seven-membered rings as potential β-ketoacyl-acyl carrier protein synthase III (FabH) inhibitors12. Issue 10 (5th August 2016) - Zhou, Yang; Luo, Yin; Yang, Yu-Shun; Lu, Liang; Zhu, Hai-Liang
Abstract : Fatty acid biosynthesis is essential for bacterial survival. Abstract : Fatty acid biosynthesis is essential for bacterial survival. FabH, β-ketoacyl-acyl carrier protein (ACP) synthase III, is a particularly attractive target, since it is central to the initiation of fatty acid biosynthesis and highly conserved among Gram-positive and Gram-negative bacteria. Following previous studies, a series of acylhydrazone derivatives with deoxygenated rings were synthesized in this work. For all of the 36 analogues synthesized, studies using H NMR, C NMR, MS and elemental analyses were conducted. Their biological activities were also evaluated against two Gram-negative bacterial strains: E. coli and P. aeruginosa, and two Gram-positive bacterial strains: B. subtilis and S. aureus by the MTT method as potential FabH inhibitors. The resulting compoundF18 showed the highest antibacterial activity with MIC values of 1.56–3.13 μg mL −1 against the tested bacterial strains and was found to be the most potent E. coli FabH inhibitor with an IC50 value of 2.0 μM. Molecular modeling simulation studies were performed in order to predict the biological activities of compoundF18 into the E. coli FabH active site.